Szacowanie bezzatrudnieniowego wzrostu gospodarczego na podstawie liniowego modelu ekonometrycznego - Łyko, Janusz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
This paper estimates relationship between the GDP and the unemployment rate for a sample of industrial countries by applying Okun's law in first differences. (short original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 297-303